A qualitative exploration of barriers in accessing community pharmacy services for persons with disability in Addis Ababa, Ethiopia: a cross sectional phenomenological study - Nebiyou Dagnachew (BMC Health Services Research, 2021)
Abstract Background It was estimated that over a billion people have a disability and around 110 to 190 million experienced significant difficulties in functioning. Similarly, there were over 5 million and 32,630 individuals with disability in Ethiopia and Addis Ababa, the capital city of Ethiopia, respectively. Health care is a human right, yet access barriers to healthcare remain one of the major challenges among people with disabilities. Community pharmacists are often the health system point of entry for most patients. Therefore, the aim of this study was to explore the barriers to community pharmacy service for individuals with physical, visual and hearing disability in Addis Ababa, Ethiopia. Methods A cross sectional phenomenological qualitative study design was employed to explore the barriers to community pharmacy service for individuals with Physical, Visual and Hearing disability. All members from Ethiopian National Association of the Blind (ENAB), Ethiopian National Association of the Deaf (ENAD) and Ethiopian National Association of persons with Physical Disability (ENAPPD) and all community pharmacy professionals in Addis Ababa were the study populations in this study. The analysis was made using content analysis where ideas were classified into themes manually. Result All informants with disability pointed out that community pharmacy services were not accessible to them. The study found transportation, physical layout, communication and medication price were the main barriers to obtain community pharmacy services among individuals with visual, physical and hearing disabilities. Respondents also witnessed that pharmacists provided proper counseling and were also cooperative and willing to help them. Conclusions This study indicated that individuals with disability experienced different access barriers to community pharmacy services. Further studies are recommended to identify other community pharmacy disparities and access barriers to pharmacy services and propose possible solutions.